The Effect Of Motivation And Family Support For Students Learning Achievement Level Ii Prodi D-III Midwifery Stikes Ubudiyah Banda Aceh - Safitri, Faradilla (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Learning achievement is the human level of the students in accepting, rejecting, and assess the information obtained in the learning process. The are many factors many factors that influence the success process in the learning, such as learning motivation and family support. Students motivation become a low, so the quality of achievement will be low. Therefore, the quality of the students learning achievement needs to be increased continuously in order for students to have a strong motivation to learn, so that the learning performance can be achieved optimally. In their family students needed theÂ support of their parents in achieving learning achievement, because the support and attention will determine the students reached aÂ high academic achievement. The purpose of this study was to determine the